PENDIDIKAN ANTI-RADIKALISME DAN STRATEGI MENGHADAPINYA (IKHTIAR MENYUSUTKAN GERAKAN RADIKALISME DI INDONESIA) - Khoiriyah Khoiriyah (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
In a study found there were three factors that caused the emergence of radicalism in Indonesia. First, radicalism develops at the global level. Both Wahhabism is spread and the third is poverty. Now a days, radicalism has been spread out in Indonesia. It has to be prohibited by anti-radicalism education. Anti-radicalism education can be preventive and anticipative effort for terorism and radicalism expansion. It will done by put anti-radicalism volues for student through learning and teaching process. In Islam concept, there is interdiction for killing and vandalism. On the contrary, Islam learns us for loving peaple/each other. It has realized on subject lesson. Anti-racalism education prosecutes youth generation to respect differentiation, to love each other, to hate vandalism and dissension. Thus, it can discontinue radicalism and terorism in Indonesia. The anthropicity of radicalism can be done through the path of the government's role, the role of religious institutions and education, the role of civil society, some critical issues, welfare approaches, the role of deradicalization, rehabilitation and reintegration. Keywords: anti-radicalism, education, Indonesia